Novel serum biomarker for powerfully predicting pediatric simple febrile seizures - Mei, Jinzhi; Hu, Chuanze; Sheng, Fang; Wang, Zhiyu; Hu, Wangxiong (Frontiers in Pediatrics, 2025)
ObjectiveCurrent model or biomarkers are far from satisfactory to predict pediatric simple febrile seizures (SFS). This study aimed to explore novel serum biomarkers in children with SFS and analyze their clinical significance.MethodsA total of 57 SFS children admitted to the pediatric ward of Jinhua Maternal and Child Health Hospital from June 2022 to October 2024 were enrolled as the observation group, 61 sepsis patients and 45 healthy children from the pediatric health clinic during the same period were included as the control groups. Serum levels of 25-hydroxyvitamin D and diverse cytokines were measured using enzyme-linked immunosorbent assay (ELISA). Univariate logistic regression was used to identify the predictive ability of risk factors for SFS.ResultsThe SFS group exhibited significantly lower levels of IL-17 (SFS: 5 vs. Health: 12 and Sepsis: 16) compared to the control groups. Conversely, the SFS group showed significantly higher levels of pro-inflammatory cytokines (IFN-α: 22 vs. 4 and 5; and IL-10: 12 vs. 10 and 9) than the control groups. ROC curve revealed that during SFS episodes, IFN-α can powerfully in discriminating SFS and health cohorts.ConclusionSerum level of IFN-α hold significant predictive value for SFS occurrence.